2005
DOI: 10.1002/eat.20163
|View full text |Cite
|
Sign up to set email alerts
|

Family physician consultation patterns indicate high risk for early‐onset anorexia nervosa

Abstract: A single consultation about eating behaviour or weight and shape concerns is a strong predictor of the subsequent emergence of anorexia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 13 publications
0
35
0
1
Order By: Relevance
“…50-90% in BN) (Johnson et al, 2001;Whitehouse et al, 1992), and that practitioners may be more likely to detect AN than BN or atypical eating disorders (Whitehouse et al, 1992); to detect eating disorders in females than in males (Currin et al, 2007); and to detect eating disorders if they themselves are female (Hugo et al, 2000). Related research has found that individuals with an identified eating disorder may attend more primary care appointments in the 5 years prior to their diagnosis than control patients over the same time frame (Lask et al, 2005;Ogg et al, 1997), suggesting that opportunities for earlier diagnosis and/or intervention may exist.…”
Section: Introductionmentioning
confidence: 97%
“…50-90% in BN) (Johnson et al, 2001;Whitehouse et al, 1992), and that practitioners may be more likely to detect AN than BN or atypical eating disorders (Whitehouse et al, 1992); to detect eating disorders in females than in males (Currin et al, 2007); and to detect eating disorders if they themselves are female (Hugo et al, 2000). Related research has found that individuals with an identified eating disorder may attend more primary care appointments in the 5 years prior to their diagnosis than control patients over the same time frame (Lask et al, 2005;Ogg et al, 1997), suggesting that opportunities for earlier diagnosis and/or intervention may exist.…”
Section: Introductionmentioning
confidence: 97%
“…75 Little is known about the service use of people with AN prior to entering treatment, but there is some evidence on elevated service use up to 5 years prior to diagnosis. 21,22 For our higher cost estimate, we draw on baseline information from the three trials analysed in Chapter 11 to estimate a plausible range of primary care costs (GP, nurse, dietitian) incurred prior to an inpatient admission or outpatient treatment. When treatment is provided exclusively in primary care, we assume that each person is in contact with their GP three times per year (NICE 2004 ED guidance 162 ).…”
Section: Primary Care Costsmentioning
confidence: 99%
“…21 A single consultation about eating or weight/shape concerns strongly predicts the subsequent emergence of AN. 22 Although GPs exclusively treat 20% of cases with AN, 23 they are often not confident at managing AN, 24 and there is usually a considerable delay between a diagnosis being made in primary care and the point when more specialist help becomes available. 25 Many parts of the UK lack NHS provision of specialist services for AN.…”
Section: Introductionmentioning
confidence: 99%
“…Even just one discussion about eating behaviour, weight or shape concerns during a consultation with a young person in a primary care setting can be a strong predictor of the subsequent development of an ED 39. Indeed, in the 5 years preceding their ED diagnosis, girls with early onset AN have been observed to visit their GP more frequently to discuss issues involving eating, weight and shape, compared with girls with other mental health problems and healthy controls 37.…”
Section: Eds—the Schoolspace Studymentioning
confidence: 99%